2017
DOI: 10.46989/001c.20886
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter aerogenes: an Emerging Pathogen for Enteritis in Farmed Channel Catfish Ictalurus punctatus

Abstract: Enteritis has caused significant economic losses in farmed channel catfish Ictalurus punctatus. Yet information is limited on Enterobacter aerogenes as a potential causal agent for enteritis in channel catfish. In this study, a virulent strain, temporarily named HT2, was isolated from diseased channel catfish suffering from enteritis, identified phenotypically and molecularly as E. aerogenes. A phylogenetic tree was constructed to examine isolate HT2 and compare it to other known isolates. In addition, isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that Acinetobacter only causes the infection of humans ( Carvalheira et al, 2021 ). But now, some members of the Acinetobacter genus can cause the diseases of fish ( Cao et al, 2016 ; Kuebutornye et al, 2020 ). Potential pathogens in the gut microbiota can cause damage when host immunity is low ( Pérez-Sánchez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Acinetobacter only causes the infection of humans ( Carvalheira et al, 2021 ). But now, some members of the Acinetobacter genus can cause the diseases of fish ( Cao et al, 2016 ; Kuebutornye et al, 2020 ). Potential pathogens in the gut microbiota can cause damage when host immunity is low ( Pérez-Sánchez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high protein content and fast growth rate, channel catfish have become a popular aquaculture crop. However, outbreaks of diseases have restricted the sustainable development of the channel catfish breeding industry and annual productivity [ 27 , 28 ]. It is urgent to investigate the molecular mechanisms beyond the immune responses of channel catfish during pathogen infection.…”
Section: Introductionmentioning
confidence: 99%